Unveiling the nexus of teacher commitment and job satisfaction: insights from Ecuador's educational landscape - Guzmán Antonio Muñoz-Fernández; Rossana Dolores Toala-Mendoza; Miguel González-Mohíno; Miryam Elizabeth Félix-López (BMC Psychology)
Abstract Understanding the factors that determine teachers’ organizational commitment and job satisfaction is fundamental in the education sector, since these two constructs are directly related to teacher effectiveness and the quality of education. Despite their importance, there is little research on these constructs in Latin America in general, and specifically in the Ecuadorian educational system. The objective of this work is thus to identify the extrinsic and intrinsic factors that influence the organizational commitment and job satisfaction of teachers in Ecuador, and to establish whether there is any relationship between organizational commitment and job satisfaction. To that end, an exploratory theoretical model based on the aforementioned variables is developed and tested on a sample of 6,316 Ecuadorian teachers, using structural equation modeling (SEM) techniques with partial least squares (PLS). The results reveal a significant relationship between both extrinsic and intrinsic factors and job satisfaction, as well as between these factors and organizational commitment. Furthermore, both extrinsic and intrinsic factors indirectly influence job satisfaction through organizational commitment. These findings underscore the importance of considering both external and internal aspects of work in efforts to promote job satisfaction and organizational commitment.